PROMOTION OF BOOKS AND READINGS - Miamlina, Antonina V. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
This research is devoted to consideration of main methods books promotion for attraction attention of readers and increase demand of relevant publications.